Improved surface and electrical properties of passivated GaSb with less alkaline sulfide solution. (December 2015) - Tao, Dongyan; Cheng, Yu; Liu, Jingming; Su, Jie; Liu, Tong; Yang, Fengyun; Wang, Fenghua; Cao, Kewei; Dong, Zhiyuan; Zhao, Youwen
Abstract: The surface quality of HCl-etched and ammonium sulfide [(NH4 )2 S]-based treated bulk n -GaSb(100) were compared using x-ray photoelectron spectroscopy (XPS) and TOF-SIMS. It has been found that native oxides present on the GaSb surface are more effectively removed when etched with concentrated HCl solution. With additional [(NH4 )2 SO4 +S] substances or hydrogen ions in the passivation solution, the treated samples displayed significant reduction of native oxides and formation of the sulfides compared with pure (NH4 )2 S solution. The treated samples also result in a noteworthy improvement in the current–voltage ( I – V ) characteristics of Au/ n -GaSb Schottky contacts, as evidenced by the lower ideality factor ( n ), higher barrier height ( Φ b ) and higher rectification ratio at ±0.2 V. The I – V measurement provided definitive confirmation of XPS and TOF-SIMS results, establishing the need for less alkaline solution for greater passivation stability.